Nursing actions in Primary Health Care to lesbian and bisexual women - Stéffane Costa Mendes; José Wagner Martins da Silva; Marlene Menezes de Souza Teixeira; Maria do Socorro Vieira Lopes (Universidade Federal do Ceará, 2023)
Objective: to investigate the actions of nurses in regard to lesbian and bisexual women in the context of the National Policy for the Integral Health of Lesbians, Gays, Bisexuals, Cross-Dressers and Transgender Persons. Methods: qualitative study involving 25 nurses from the Family Health Strategy, contacted via electronic means. We applied a form containing sociodemographic data and an investigation of actions in primary health care, as well as a thematic content analysis. Results: we found there are professional capacitation activities, embracing of demands, and enhanced interprofessional work. Nonetheless, there were shortcomings in the knowledge regarding health care towards lesbian and bisexual women. Conclusion: there are still prejudices, difficulty to access, and little attendance of lesbian and bisexual women in health services, as well as a deficit in the support to health actions and lack of monitoring. Contributions to practice: the importance of the scientific, professional, and social experiences stand out, regarding the need to humanize the care to lesbian and bisexual women. It is a supporting material for researchers and nursing professionals, enabling them to direct their care to a holistic and integral care to be provided to these women, in addition to being an encouragement to further comparative studies.